(untitled) (Global Journal of Science Frontier Research, 2018)
The theory that the universe is growing and expanding to oblivion, which has become more of a conclusion by mainstream science, has two problems that seem to be insurmountable. First and foremost is that this theory is based on such a small sample size, 4% of the known total, any findings based on such a small sample size of the total is subject to very questionable credibility no matter what your evidence. This entire arena of inquiry is without foundation given dark matter/dark energy (DM/DE) represent 96% of the subject under investigation, it is unknown and has no workable model to use for understanding its nature and makeup. Second, there is no map, no theory that unifies the functional and structural components to give a vision which leads to an understanding of the dynamics of the known expanse of our cosmos from the Planck quantum scale 10^-35to the Newtonian based galactic scale 10^35; that can be used as a model or framework for evaluation, comparison and analysis of observational and experimental data collected. I am purposing such a model. This is a workable model that reveals a theory that allows definition and explanation of the great cosmic expanse and it reveals that what our current observations are showing that leads to the widespread opinion that the universe is expanding and even accelerating is possibly being misinterpreted. This is in part because of the two problems mentioned above. What is interpreted as expansion is in all probably actually a flow.